Você penduraria essa fotografia na sala de estar da sua casa? : aproximações à fotografia erótica latino-americana - Giraldo Bareño, César Augusto (2018)
The dissertation seeks to approximate the relationship between eroticism and photography in the Latin American context. Concept and technique (eroticism and photography) they have a long relationship history that the work tries to explain until arriving a